Multi-defect hydrotalcite material as well as preparation method and application thereof
By introducing bimetal doping and alkali etching technology on hydrotalcite nanosheets, multi-defect hydrotalcite materials were designed, which solved the problems of instability and low bioavailability of existing antioxidants in the treatment of stroke reperfusion injury. Achieve stronger antioxidant activity and better therapeutic effects.
Patent Information
- Application Number
- CN202411590239.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-11
AI Technical Summary
Existing antioxidants have problems such as instability, low bioavailability and difficulty in crossing the blood-brain barrier in the treatment of stroke reperfusion injury, which limits their clinical application.
By introducing defect engineering technologies such as bimetal doping and alkali etching, multi-defect hydrotalcite nanosheets were designed to enhance their antioxidant activity and regulate their electronic structures, and improve bioavailability.
When encountering reactive oxygen species, this material has stronger free radical scavenging ability, effectively alleviating oxidative stress response, and improving the therapeutic effect on stroke reperfusion injury.
Smart Images

Figure CN119409225A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of cerebral stroke drugs, and more specifically, to a multi-defect hydrotalcite material and a preparation method and application thereof. Background Art
[0002] Stroke is the leading cause of death and disability in the adult population in my country. It has the characteristics of high morbidity, high disability rate and high mortality rate. Among them, acute ischemic stroke accounts for 71% (Nature Reviews Disse Primers, 2019, 5, 70). When acute ischemic stroke occurs, the blood supply to the brain is interrupted, cutting off the transport of oxygen and nutrients, thereby causing neuronal death, inflammation and neurovascular damage, leading to severe neurological symptoms. Stroke causes damage to the core and penumbra. The cells in the core area of the infarction are irreversibly damaged within a few minutes and cannot be saved; the penumbra is located between the core and healthy brain tissue. If reperfusion is established early, the cells in the penumbra are salvageable. However, with the reperfusion of the infarct area, it will lead to oxidative stress, inflammation, excitotoxicity and other mechanisms, which are very likely to damage neurons and glial cells, leading to neuronal apoptosis or necrosis and blood-brain barrier destruction. Among them, oxidative stress damage is one of the core pathological causes of reperfusion injury, which is caused by the production of a large amount of reactive oxygen species (ROS). ROS include hydrogen peroxide (H2O2), superoxide anion (·O2 – ) and hydroxyl radicals (·OH), which mediate oxidative stress and induce excessive inflammatory response, impairing neurological function, thus seriously affecting the patient's prognosis (Journal of Experimental Medicine, 2008, 205, 1227-1242). In recent years, neuroprotective agents such as edaravone and dextroborneol have shown the efficacy of scavenging free radicals, inhibiting inflammatory cytokines, and reducing infarct volume as clinical drugs, but these drugs still have a series of problems such as instability, low bioavailability, poor ability to penetrate the blood-brain barrier, and a single mechanism of action, which limits their clinical application.
[0003] In recent years, catalytically active nanomaterials have provided a new solution for treating oxidative stress injury caused by stroke reperfusion. Compared with traditional antioxidants, nanomaterials have higher stability and catalytic activity, and through nanoscale design, they are expected to overcome the limitations of the blood-brain barrier. However, how to further enhance the antioxidant activity of nanomaterials and reduce oxidative stress response remains one of the core research issues. Structural optimization of nanomaterial catalysts through defect engineering, such as introducing oxygen vacancies, metal doping or other structural defects, can significantly enhance their antioxidant activity and prolong their bioavailability in the body. However, how to further enhance their antioxidant activity through reasonable defect structure design remains a key challenge to be solved in future research. Summary of the invention
[0004] Based on the above facts, the purpose of the present invention is to provide a multi-defect hydrotalcite material and a preparation method and application thereof, so that the nanomaterial can be better used in the preparation of stroke drugs and better play its role.
[0005] On the one hand, the present invention provides a multi-defect hydrotalcite material, wherein the structure of the material comprises bimetallic doped magnesium vanadium hydrotalcite nanosheets and the multi-defect hydrotalcite material after alkali etching.
[0006] In this technical solution, the bimetallic doped elements are evenly dispersed on the magnesium vanadium hydrotalcite, the surface of the layer plate has abundant hydroxyl groups and positive charges, and the interlayer has negative charges. After alkali etching, part of the doped metal is separated from the layer plate, and a large number of metal vacancies and part of oxygen vacancies are formed on the layer plate.
[0007] In the technical solution, the defective hydrotalcite nanosheets have more dispersed lamellae and smaller particle size than bimetallic-doped magnesium-vanadium hydrotalcite.
[0008] Furthermore, in the magnesium-vanadium hydrotalcite nanosheets, the molar ratio of magnesium to vanadium is (0.5-3): 1. Exemplary ratios include but are not limited to (0.5-1.5): 1, (2-3): 1, 1.4: 1, and the like.
[0009] Furthermore, the molar content of the doped metal salt solution is 1-10% of the total molar content of magnesium and vanadium. Exemplarily, the molar ratio of the total amount of magnesium and vanadium to the doped metal in the bimetallic doped magnesium vanadium hydrotalcite nanosheets is 1:0.02-1:0.1, 1:0.02-1:0.5, 1:0.02-1:0.025, 1:0.02-1:0.04, 1:0.025-1:0.1, etc.
[0010] Furthermore, the size of the bimetallic doped magnesium vanadium hydrotalcite nanosheets is 50 nm to 500 nm, and exemplary sizes include but are not limited to 50 to 120 nm, 200 to 300 nm, 250 to 500 nm, 300 nm, and the like.
[0011] Furthermore, the size of the multi-defect hydrotalcite material is 30 nm to 100 nm, and exemplary sizes include but are not limited to 30 to 100 nm, 50 to 100 nm, 80 nm, and the like.
[0012] In another aspect, the present invention provides a method for preparing the defective hydrotalcite nanosheets as described above, comprising the following steps:
[0013] Providing bimetallic doped magnesium vanadium hydrotalcite nanosheets;
[0014] The bimetallic doped magnesium vanadium hydrotalcite nanosheets are mixed with an alkaline solution, stirred, centrifuged, washed and dried under light-proof conditions to obtain the multi-defect hydrotalcite nanomaterial. The reaction time is 1 to 5 hours and the reaction temperature is 25 to 60°C.
[0015] Furthermore, the alkaline substance is selected from sodium hydroxide, potassium hydroxide, and ammonia water, and the selected alkali concentration is 0.5-8M.
[0016] Furthermore, the bimetallic doped magnesium vanadium hydrotalcite nanosheets can be prepared by conventional methods in the art. Alternatively, the preparation of the bimetallic doped magnesium vanadium hydrotalcite comprises the following steps:
[0017] Magnesium nitrate, vanadium trichloride, a doped metal salt solution and a solution of an alkaline substance are mixed and put into a reactor for reaction to obtain a dual-doped magnesium-vanadium hydrotalcite.
[0018] Furthermore, the alkaline substance is selected from sodium hydroxide.
[0019] Furthermore, the doping metal salt is selected from two of zinc nitrate, gallium nitrate, aluminum nitrate and nickel nitrate.
[0020] Furthermore, the reaction temperature is 60-180° C., the reaction time is 5-12 hours, and the reaction is carried out in a reactor.
[0021] In another aspect, the present invention provides use of the defective hydrotalcite nanosheets as described above in a stroke drug.
[0022] Unless otherwise specified, various raw materials used in the present invention can be purchased commercially or obtained by conventional means in the art.
[0023] The beneficial effects of the present invention are as follows:
[0024] In the multi-defect hydrotalcite provided by the present invention, a large number of metal vacancies constructed by alkali etching will readjust the electronic structure of the hydrotalcite nanosheets, reduce the valence state of the active center vanadium through the charge compensation effect, so that the defective hydrotalcite nanosheets have good antioxidant activity, and the magnesium in the layer plate has high biosafety. When the material encounters a large number of active oxygen species, the vanadium element will provide redox properties through valence changes, converting active oxygen into non-toxic H2O and O2, effectively reducing oxidative stress reactions when stroke reperfusion injury occurs, and treating brain damage.
[0025] The invention provides a method for preparing a defective hydrotalcite material, wherein a dual-doped magnesium-vanadium hydrotalcite nanosheet is used as a template and alkali etching is performed to prepare the defective hydrotalcite material. The preparation method has simple process, low energy consumption, low equipment requirements and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0027] Figure 1 This is a transmission electron microscope image of the dual-doped magnesium vanadium hydrotalcite nanosheets synthesized in Example 1.
[0028] Figure 2 This is a transmission electron microscope image of the multi-defective hydrotalcite nanosheets synthesized in Example 1.
[0029] Figure 3 V 2p spectra of X-ray photoelectron spectra of the dual-doped hydrotalcite nanosheets and multi-defect hydrotalcite nanosheets synthesized in Example 1.
[0030] Figure 4 The ROS scavenging efficiency diagrams of the dual-doped magnesium vanadium talc nanosheets and multi-defect hydrotalcite nanosheets synthesized in Example 1 are shown in Figure (a) for scavenging hydroxyl radical efficiency diagrams, and Figure (b) for scavenging superoxide radical efficiency diagrams.
[0031] Figure 5 This is a TTC staining image of the dual-doped magnesium vanadium talc nanosheets and multi-defect hydrotalcite nanosheets synthesized in Example 1 for the treatment of stroke reperfusion injury. DETAILED DESCRIPTION
[0032] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0033] Example 1
[0034] A preparation method of a multi-defect hydrotalcite nanosheet composite material comprises the following steps:
[0035] 1) 1.79 g of magnesium nitrate hexahydrate, 0.472 g of vanadium trichloride, 0.089 g of zinc nitrate hexahydrate, and 0.076 g of gallium nitrate hydrate were dissolved in 40 mL of water and mixed to obtain liquid A; 0.8 g of sodium hydroxide was dissolved in 40 mL of water and mixed to obtain liquid B; under stirring at room temperature, liquid A and liquid B were simultaneously added dropwise to a flask, the pH was adjusted to 10, and then the solution was placed in a reactor at 100° C. and reacted for 10 hours, then the reactant was taken out and centrifuged, washed, and dried to obtain dual-doped hydrotalcite nanosheets.
[0036] 2) The dual-doped hydrotalcite nanosheets obtained in step 1) are dispersed in a 4M sodium hydroxide solution, stirred at 25° C. for 3 h, centrifuged, washed, and dried to obtain a multi-defect hydrotalcite nanomaterial.
[0037] The transmission electron microscope image of the dual-doped hydrotalcite nanosheet material prepared by the above preparation method is as follows: Figure 1 In this embodiment, the transmission electron microscope image of the multi-defect hydrotalcite material prepared is as shown in Figure 2 shown. Figure 1 It shows that multiple pieces of zinc-gallium-doped magnesium-vanadium hydrotalcite are aggregated together, and the aggregate size is about 200nm. Figure 2 The multi-defect hydrotalcite material shown in the figure is about 50 nm in size, and the multi-defect hydrotalcite material after etching is in a dispersed state. The zinc-gallium dual-doped magnesium-vanadium hydrotalcite and the multi-defect hydrotalcite nanomaterials obtained by etching were dried and tested for X-ray photoelectron spectroscopy. Figure 3 As shown, after etching V 5+ The ratio of V 3+ and V 4+ The increase in the ratio of proves the charge compensation regulation caused by the generation of metal vacancies after etching. Figure 4 As shown in (a), 1.8 mM ferrous sulfate heptahydrate and 4.9 mM hydrogen peroxide aqueous solution were prepared as the conditions for generating hydroxyl radicals, and then 500 μg / mL zinc-gallium dual-doped magnesium-vanadium hydrotalcite or multi-defective hydrotalcite was added to test the ability to capture hydroxyl radicals using an ultraviolet spectrophotometer. Figure 4 As shown in (b), 0.6 mM xanthine, 0.3 U / mL xanthine oxidase and 500 μg / mL sample were mixed in a pH 7.4 PBS buffer, and 100 μg / mL NBT indicator was added to the solution. After 3 minutes of reaction, the ability to scavenge superoxide radicals was tested using a UV spectrophotometer. Through the UV absorption spectrum, it can be seen that the etched multi-defect nanomaterials show stronger free radical scavenging ability. Figure 5 As shown, by using dual-doped hydrotalcite nanosheets and multi-defective hydrotalcite materials to treat stroke-reperfusion mice, TTC staining showed that the infarct area was the smallest after multi-defective hydrotalcite treatment, indicating that defective hydrotalcite materials have a good effect in treating reperfusion injury.
[0038] Example 2
[0039] A preparation method of a multi-defect hydrotalcite nanosheet composite material comprises the following steps:
[0040] 1) Dissolve 1.79 g of magnesium nitrate hexahydrate, 0.472 g of vanadium trichloride, 0.089 g of zinc nitrate hexahydrate, and 0.076 g of gallium nitrate hydrate in 40 mL of water and mix them evenly to obtain liquid A; dissolve 0.8 g of sodium hydroxide in 40 mL of water and mix them evenly to obtain liquid B; add liquid A and liquid B dropwise into a flask at room temperature with stirring, adjust the pH to 10, and then put the solution into a reactor at 180° C., react for 12 hours, take out the reactant, centrifuge, wash, and dry to obtain dual-doped hydrotalcite nanosheets.
[0041] 2) The dual-doped hydrotalcite nanosheets obtained in step 1) are dispersed in a 4M sodium hydroxide solution, stirred at 30° C. for 3 h, centrifuged, washed, and dried to obtain a multi-defect hydrotalcite nanomaterial.
[0042] The obtained dual-doped magnesium vanadium hydrotalcite sheets are aggregated together, and the aggregate size is about 500nm. The obtained multi-defect hydrotalcite nanosheets after etching have a nanosheet size of about 80nm. They are weighed to form a 500μg / mL dispersion, and the ROS scavenging effect and the therapeutic ability of treating stroke reperfusion injury mice are detected by the method of Example 1. The obtained multi-defect hydrotalcite material has higher hydroxyl radical and superoxide anion scavenging effect and ability to reduce cerebral infarction area than the dual-doped hydrotalcite nanosheets.
[0043] Example 3
[0044] A preparation method of a multi-defect hydrotalcite nanosheet composite material comprises the following steps:
[0045] 1) 1.79 g of magnesium nitrate hexahydrate, 0.472 g of vanadium trichloride, 0.089 g of zinc nitrate hexahydrate, and 0.076 g of gallium nitrate hydrate were dissolved in 40 mL of water and mixed to obtain liquid A; 0.8 g of sodium hydroxide was dissolved in 40 mL of water and mixed to obtain liquid B; under stirring at room temperature, liquid A and liquid B were simultaneously added dropwise to a flask, the pH was adjusted to 10, and then the solution was placed in a reactor at 100° C. and reacted for 10 hours, then the reactant was taken out and centrifuged, washed, and dried to obtain dual-doped hydrotalcite nanosheets.
[0046] 2) The dual-doped hydrotalcite nanosheets obtained in step 1) are dispersed in a 6M sodium hydroxide solution, stirred at 30° C. for 5 h, centrifuged, washed, and dried to obtain a multi-defect hydrotalcite nanomaterial.
[0047] The obtained dual-doped magnesium vanadium hydrotalcite sheets are aggregated together, and the aggregate size is about 200nm. The obtained multi-defect hydrotalcite nanosheets after etching have a nanosheet size of about 30nm. They are weighed to form a 500μg / mL dispersion, and the ROS scavenging effect and the therapeutic ability of treating stroke reperfusion injury mice are detected by the method of Example 1. The obtained multi-defect hydrotalcite material has higher hydroxyl radical and superoxide anion scavenging effect and ability to reduce cerebral infarction area than the dual-doped hydrotalcite nanosheets.
[0048] Example 4
[0049] Example 1 was repeated, except that the step 1) "1.79 g of magnesium nitrate hexahydrate, 0.472 g of vanadium trichloride, 0.089 g of zinc nitrate hexahydrate, and 0.076 g of hydrated gallium nitrate were dissolved in 40 mL of water and mixed evenly to form liquid A" was replaced with "1.79 g of magnesium nitrate hexahydrate, 0.944 g of vanadium trichloride, 0.178 g of zinc nitrate hexahydrate, and 0.152 g of hydrated gallium nitrate were dissolved in 40 mL of water and mixed evenly to form liquid A". The other conditions remained unchanged, and dual-doped hydrotalcite nanosheets and multi-defect hydrotalcite nanomaterials were prepared. The size of the obtained dual-doped magnesium vanadium hydrotalcite was about 200 nm, and the size of the obtained multi-defect hydrotalcite nanosheets after etching was about 30 nm. It was weighed into a 500 μg / mL dispersion, and the ROS scavenging effect and the therapeutic ability to treat stroke reperfusion injury in mice were detected by the method as in Example 1. The obtained multi-defective hydrotalcite material had higher hydroxyl radical and superoxide anion scavenging effect and ability to reduce cerebral infarction area compared with the dual-doped hydrotalcite nanosheets.
[0050] Example 5
[0051] Example 1 was repeated, except that the step 1) of "1.79 g of magnesium nitrate hexahydrate, 0.472 g of vanadium trichloride, 0.089 g of zinc nitrate hexahydrate, and 0.076 g of hydrated gallium nitrate were dissolved in 40 mL of water and mixed evenly to form liquid A" was replaced with "1.79 g of magnesium nitrate hexahydrate, 0.472 g of vanadium trichloride, 0.089 g of zinc nitrate hexahydrate, and 0.113 g of magnesium nitrate hexahydrate were dissolved in 40 mL of water and mixed evenly to form liquid A". The other conditions remained unchanged, and dual-doped hydrotalcite nanosheets and multi-defect hydrotalcite nanomaterials were prepared. The size of the obtained dual-doped magnesium vanadium hydrotalcite was about 200 nm, and the size of the obtained multi-defect hydrotalcite nanosheets after etching was about 30 nm. It was weighed into a 500 μg / mL dispersion, and the ROS scavenging effect and the therapeutic ability to treat stroke reperfusion injury in mice were detected by the method as in Example 1. The obtained multi-defective hydrotalcite material had higher hydroxyl radical and superoxide anion scavenging effect and ability to reduce cerebral infarction area compared with the dual-doped hydrotalcite nanosheets.
[0052] Example 6
[0053] Example 1 was repeated, except that the step 1) "1.79 g of magnesium nitrate hexahydrate, 0.472 g of vanadium trichloride, 0.089 g of zinc nitrate hexahydrate, and 0.076 g of hydrated gallium nitrate were dissolved in 40 mL of water and mixed to form liquid A" was replaced with "1.05 g of magnesium nitrate hexahydrate, 0.472 g of vanadium trichloride, 0.087 g of nickel nitrate hexahydrate, and 0.113 g of magnesium nitrate hexahydrate were dissolved in 40 mL of water and mixed to form liquid A". The other conditions remained unchanged, and dual-doped hydrotalcite nanosheets and multi-defect hydrotalcite nanomaterials were prepared. The size of the obtained dual-doped magnesium vanadium hydrotalcite was about 200 nm, and the size of the obtained multi-defect hydrotalcite nanosheets after etching was about 30 nm. It was weighed into a 500 μg / mL dispersion, and the ROS scavenging effect and the therapeutic ability to treat stroke reperfusion injury in mice were detected by the method as in Example 1. The obtained multi-defective hydrotalcite material had higher hydroxyl radical and superoxide anion scavenging effect and ability to reduce cerebral infarction area compared with the dual-doped hydrotalcite nanosheets.
[0054] Example 7
[0055] Example 1 was repeated, except that the phrase "then the solution was placed in a reactor at 100°C and reacted for 10 hours" in step 1) was replaced with "then the solution was placed in a reactor at 60°C and reacted for 6 hours". The other conditions remained unchanged, and dual-doped hydrotalcite nanosheets and multi-defect hydrotalcite nanomaterials were prepared. The size of the dual-doped magnesium vanadium hydrotalcite obtained was about 150 nm, and the size of the multi-defect hydrotalcite nanosheets obtained after etching was about 30 nm. It was weighed and prepared into a dispersion of 500 μg / mL, and the ROS scavenging effect and the therapeutic ability to treat mice with stroke reperfusion injury were detected by the method as in Example 1. The multi-defect hydrotalcite material obtained had a higher hydroxyl radical and superoxide anion scavenging effect and the ability to reduce the area of cerebral infarction than the dual-doped hydrotalcite nanosheets.
[0056] Example 8
[0057] Example 1 was repeated, except that the step 2) "then the solution was placed in a reactor at 100°C and reacted for 10 hours" was replaced with "then the solution was placed in a reactor at 60°C and reacted for 6 hours". The other conditions remained unchanged, and dual-doped hydrotalcite nanosheets and multi-defect hydrotalcite nanomaterials were prepared. The size of the dual-doped magnesium vanadium hydrotalcite obtained was about 150nm, and the size of the multi-defect hydrotalcite nanosheets obtained after etching was about 30nm. It was weighed and prepared into a dispersion of 500μg / mL, and the ROS scavenging effect and the therapeutic ability of treating stroke reperfusion injury in mice were detected by the method as in Example 1. The obtained multi-defect hydrotalcite material had higher hydroxyl radical and superoxide anion scavenging effect and ability to reduce cerebral infarction area compared with dual-doped hydrotalcite nanosheets.
[0058] Example 9
[0059] Example 2 was repeated, except that "the obtained dual-doped hydrotalcite nanosheets were dispersed in 4M hydroxide solution at 25°C and stirred for 3h" in step 2) was replaced by "the obtained dual-doped hydrotalcite nanosheets were dispersed in 3M hydroxide solution at 30°C and stirred for 3h". "The solution was then placed in a reactor at 100°C and reacted for 10h" in step 1) was replaced by "the solution was then placed in a reactor at 150°C and reacted for 10h". The other conditions remained unchanged, and dual-doped hydrotalcite nanosheets and multi-defect hydrotalcite nanomaterials were prepared. The size of the obtained dual-doped magnesium vanadium hydrotalcite was about 350nm, and the size of the obtained multi-defect hydrotalcite nanosheets after etching was about 70nm. It was weighed into a 500 μg / mL dispersion, and the ROS scavenging effect and the therapeutic ability to treat stroke reperfusion injury in mice were detected by the method as in Example 1. The obtained multi-defective hydrotalcite material had higher hydroxyl radical and superoxide anion scavenging effect and ability to reduce cerebral infarction area compared with the dual-doped hydrotalcite nanosheets.
[0060] Example 10
[0061] Example 1 was repeated, except that "dispersed in 4M sodium hydroxide solution" in step 2) was replaced by "dispersed in 4M potassium hydroxide solution". The other conditions remained unchanged, and dual-doped hydrotalcite nanosheets and multi-defect hydrotalcite nanomaterials were prepared. The size of the dual-doped magnesium vanadium hydrotalcite obtained was about 200nm, and the size of the multi-defect hydrotalcite nanosheets obtained after etching was about 50nm. It was weighed into a dispersion of 500μg / mL, and the ROS scavenging effect and the therapeutic ability of treating mice with stroke reperfusion injury were detected by the method as in Example 1. The obtained multi-defect hydrotalcite material had higher hydroxyl radical and superoxide anion scavenging effect and ability to reduce cerebral infarction area compared with dual-doped hydrotalcite nanosheets.
[0062] Embodiment 11
[0063] Example 1 was repeated, except that "dispersed in 4M sodium hydroxide solution" in step 2) was replaced by "dispersed in 4M ammonia solution". The other conditions remained unchanged, and dual-doped hydrotalcite nanosheets and multi-defect hydrotalcite nanomaterials were prepared. The size of the dual-doped magnesium vanadium hydrotalcite obtained was about 200nm, and the size of the multi-defect hydrotalcite nanosheets obtained after etching was about 100nm. It was weighed into a dispersion of 500μg / mL, and the ROS scavenging effect and the therapeutic ability of treating mice with stroke reperfusion injury were detected by the method of Example 1. The obtained multi-defect hydrotalcite material had higher hydroxyl radical and superoxide anion scavenging effect and ability to reduce cerebral infarction area compared with dual-doped hydrotalcite nanosheets.
[0064] Comparative Example 1
[0065] The preparation method is basically the same as that in Example 1, except that the "magnesium nitrate hexahydrate" in 1) is replaced by "magnesium sulfate" and the other conditions remain unchanged. Multi-defective hydrotalcite nanosheets of about 50 nm cannot be obtained.
[0066] Comparative Example 2
[0067] The preparation method is basically the same as that in Example 1, except that "adjusting the pH to 10" in 1) is replaced by "adjusting the pH to 7", and the other conditions remain unchanged, and no dual-doped magnesium vanadium hydrotalcite nanosheets are obtained.
[0068] Comparative Example 3
[0069] The preparation method is basically the same as that in Example 1, except that "dispersed in 4M sodium hydroxide solution" in 2) is replaced by "dispersed in 4M acidic solution", and the other conditions remain unchanged. No multi-defect hydrotalcite material is obtained.
[0070] Comparative Example 4
[0071] The preparation method is basically the same as that in Example 1, except that the "vanadium trichloride" in 1) is replaced with "aluminum nitrate hexahydrate", and the other conditions remain unchanged to obtain magnesium aluminum hydrotalcite nanosheets. However, the ROS scavenging experiment found that the hydrotalcite without vanadium has no effect in scavenging ROS.
[0072] Comparative Example 5
[0073] The preparation method is basically the same as that in Example 1, except that the "4M sodium hydroxide solution" in 2) is replaced by "10M sodium hydroxide solution" and the other conditions remain unchanged. No multi-defective hydrotalcite nanomaterial is obtained.
[0074] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A multi-defect hydrotalcite material, characterized in that: The structure of the material comprises bimetallic doped magnesium vanadium hydrotalcite nanosheets and defective hydrotalcite nanosheets treated with alkali etching; the molar ratio of magnesium to vanadium in the bimetallic doped magnesium vanadium hydrotalcite nanosheets is 0.5 to 3 / 1; the molar content of the doped metal salt solution is 1 to 10% of the total molar content of magnesium and vanadium.
2. The multi-defect hydrotalcite material according to claim 1, characterized in that: The size of the bimetallic doped magnesium vanadium hydrotalcite nanosheets is 50nm to 500nm.
3. The multi-defect hydrotalcite material according to claim 1, characterized in that: The size of the defective hydrotalcite nanosheets is 30nm to 100nm.
4. The method for preparing defective hydrotalcite nanosheets according to any one of claims 1 to 3, characterized in that: The steps include: Providing dual-doped magnesium-vanadium hydrotalcite nanosheets; The bimetallic doped magnesium vanadium hydrotalcite nanosheets are mixed with an alkaline solution, and then stirred, centrifuged, washed and dried under light-proof conditions to obtain the defective hydrotalcite nanosheets.
5. The preparation method according to claim 4, characterized in that: The alkaline solution for etching the defective hydrotalcite nanosheets is selected from sodium hydroxide, potassium hydroxide and ammonia water, and the concentration of the alkali is 0.5-8M.
6. The preparation method according to claim 5, characterized in that: The time for etching the defective hydrotalcite nanosheets with an alkaline solution is 1 to 5 hours, and the temperature is 25 to 60°C.
7. The preparation method according to claim 5, characterized in that: The preparation of the bimetallic doped magnesium vanadium hydrotalcite nanosheets comprises the following steps: Magnesium nitrate, vanadium trichloride, a doped metal salt solution and a solution of an alkaline substance are mixed, put into a reactor for reaction, centrifuged, washed and dried to obtain a dual-doped magnesium-vanadium hydrotalcite.
8. The preparation method according to claim 7, characterized in that: The doping metal salt is selected from two of zinc nitrate, gallium nitrate, aluminum nitrate and nickel nitrate.
9. The preparation method according to claim 7, wherein the reaction temperature is 60-180°C, the reaction time is 5-12 hours, and the reaction is carried out in a reactor.
10. Use of the defective hydrotalcite nanosheets according to any one of claims 1 to 3 in the preparation of a stroke drug.